2003
DOI: 10.1254/jphs.93.437
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Nasal Hyperresponsiveness Aggravates Antigen-Induced Rhinitis in the Guinea Pig

Abstract: Abstract. Whether a state of nasal hyperresponsiveness influences antigen-induced biphasic nasal blockage and sneezing were examined using a guinea pig model of allergic rhinitis. Sensitized animals were challenged with an antigen, Japanese cedar pollen, once every week. Before the 13th challenge, the animals were randomly divided into 2 groups, and then the 13th challenge was performed (Groups A-0 and B-0). The 14th challenge was done on day 2 (Group A-2) and on day 7 (Group B-7) after the 13th challenge, on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…25,26) Moreover, nasal hyperresponsiveness to histamine gradually developed in response to pollen inhalation in clinical observation 27) and in an animal model. 28) Our results showed that repeated administration of epinastine and ramatroban significantly inhibited the increase of histamine hypersensitivity in the model of allergic rhinitis. The prophylactic effects of epinastine on seasonal allergic rhinitis in human were investigated, and the results of the present study corresponded with those of these clinical studies.…”
Section: Discussionmentioning
confidence: 53%
“…25,26) Moreover, nasal hyperresponsiveness to histamine gradually developed in response to pollen inhalation in clinical observation 27) and in an animal model. 28) Our results showed that repeated administration of epinastine and ramatroban significantly inhibited the increase of histamine hypersensitivity in the model of allergic rhinitis. The prophylactic effects of epinastine on seasonal allergic rhinitis in human were investigated, and the results of the present study corresponded with those of these clinical studies.…”
Section: Discussionmentioning
confidence: 53%
“…The numbers of sneezing and nasal rubbing events were counted for 20 minutes following nasal challenge. Sneezing was characterized by an explosive expiration after deep inspiration (Mizutani et al, 2003), and nasal rubbing was characterized by nasal scratching with forelimbs. As a control, 10% ethanol was instilled.…”
Section: Methodsmentioning
confidence: 99%
“…Ovalbumin was obtained from Sigma Chemical Co. (St. Louis, MO, USA). Al(OH) 3 gels were prepared with 0.5 N NaOH and 0.5 N Al 3 (SO 4 ) 3 as preciously described (12), which were a modification of the method of Levine and Vaz (13).…”
Section: Methodsmentioning
confidence: 99%